Prática avançada de Enfermagem: reflexões para subsidiar a implementação na atenção primária a saúde brasileira - Melo, Marjorie Dantas Medeiros (2021)
In view of the growing global dimension on the strengthening of Primary Health Care through the expansion and training of human resources, especially in nursing, it is essential to present the role of Advanced Practice Nursing and its potential for transformation in Primary Health Care in Brazil. The objective of this study is to analyze Advanced Practice Nursing, focusing on the role of Family Nurse Practitioners, in order to support reflections for the implementation in Brazilian Primary Health Care. This is a multi-method study with three stages, with a conceptual focus on the PEPPA framework, described below: Literature review on the impact of the management of Advanced Practice Nurses on NonCommunicable Diseases in Primary Health Care; Case study with Family Nurse Practitioners in the USA; Theoretical-Philosophical Essay in light of Max Horkheimer's Critical Theory where the following reflections guided the study: What is the contribution of Critical Theory to the discipline of Nursing? How to relate the main concepts of Max Horkheimer's Critical Theory with nursing praxis? Can advancedpractice nursing be an instrument on the path to social transformation by increasing universal access to health? In step 1, it was possible to verify the positive impact that advanced nursing practice has on the four most frequent categories of Noncommunicable Diseases, namely: Diabetes, Cardiovascular Diseases, Chronic Respiratory Diseases and Cancer. In step 2, from the analysis of the interviews conducted with the Family Nurse Practitioner in the USA, three partitions emerged based on the content of the participants' statements: 1) Being an advanced practice nurse; 2) Educational routes and possibilities of action and 3) Being political: a path for transformation, where it was possible to describe competences and skills considered to be outstanding points in relation to other professional categories, points of improvement in their educational background and the importance of political representation and being active in performing the role. In the last stage of the research, the emergence of a change in the scenario of primary health care in Brazil was highlighted, placing nurses as a primary tool in the struggle for social transformation and the search for autonomy as citizens and professionals in the light of Critical Theory and its concepts. The complexity of the nurse's work dialogues with the concepts of Critical Theory and stimulates critical behavior towards praxis in knowledge / action, strengthening its function. At the present time, it is biased to expand the practice of nurses through the implementation of Advanced Nursing Practice as one of the possible solutions for the reduction of social inequalities caused by the lack of equal access to health. It is expected through this study, to subsidize the implementation of Advanced Nursing Practice in the context of Primary Health Care, along the lines of the PEPPA framework, by understanding what Advanced Nursing Practice is in the scope of family health, reflecting about the path taken so far and the next steps to be taken, always in the constant search for recognition, autonomy and transformation.